A theoretical framework for research and development into sound online learning in higher education. - Siragusa, Lou; Dixon, Kathryn (Australian Association for Research in Education 'AARE', 2005)
The development of sound instructional design principles for online learning in higher education needs to draw from the vast body of literature which reports on the findings of research into instructional technologies, cognitive learning theories and adult education (Reeves & Reeves, 1997). A recent study by Siragusa (2005) examined the body of literature which was derived from three main discipline areas that provide a theoretical framework for the potential development of a model for online learning in higher education. From these three main discipline areas, seven distinct focus areas have been identified as having direct influence on the research, design and delivery of effective online learning environments. This paper outlines each of these focus areas and argues the importance of this theoretical base for research and development into pedagogically effective online learning environments in higher education.